Waterpipe dependence in university students and effect of normative beliefs: a cross-sectional study. Issue 2 (14th February 2014) - Salameh, P; Salamé, J; Waked, M; Barbour, B; Zeidan, N; Baldi, I
Abstract : Objectives: The objective of this study was to measure the correlates, including normative beliefs, associated with waterpipe (WP) and cigarette smoking prevalence and dependence. Setting: A cross-sectional study was carried out using a proportionate cluster sample of Lebanese students in 17 public and private universities. Participants: Of the 4900 distributed questionnaires, 3384 (69.1%) were returned to the field worker. All available students during break times were approached, with no exclusion criteria. Primary and secondary outcome measures: sociodemographic variables, detailed active and passive smoking, in addition to items of the tobacco dependence scales were all evaluated. Results: Correlates to WP smoking were studying in a private university (adjusted OR, aOR=1.50 (1.26 to 1.79); p<0.001) and ever smoking cigarettes (aOR=1.80(1.44 to 2.26); p<0.001); friends' and societal influence were found on smoking behaviour and dependence. Although the role of parents was not visible in decreasing the risk of smoking WP, their protective influence seemed more important on WP dependence (β=−1.09(−1.79 to −0.28); p<0.001), a behaviour that is considered more deleterious for health. Parents' and friends' disagreement with smoking had a protective effect on cigarette smoking and dependence (aOR<1; p<0.01), while thinking that idols and successful people smoke increased the risk of both cigarette smoking and dependence (aOR>1; p<0.01). Conclusions: In conclusion, WP smoking and dependence are influenced by parents' and friends' opinions, and idols' smoking status. Future research is necessary to further improve our understanding of motives for WP smoking and dependence.